Response to anti-programmed cell death protein-1 antibodies in men treated for platinum refractory germ cell cancer relapsed after high-dose chemotherapy and stem cell transplantation - Zschäbitz, Stefanie; Lasitschka, Felix; Hadaschik, Boris; Hofheinz, Ralf-Dieter; Jäger, Dirk; Grüllich, Carsten (European journal of cancer, 2017)
Introduction: Treatment options for patients with platinum refractory metastatic germ cell tumours (GCT) relapsing after high-dose chemotherapy and autologous stem cell transplantation are limited and survival is poor. Antibodies directed against programmed cell death protein-1 (PD-1) and programmed cell death ligand-1 (PD-L1) are currently assessed within clinical trials. We present updated data on our experience with checkpoint inhibitors as a compassionate use off-label treatment attempt for highly-pretreated patients with GCT and provide an overview of the current literature on PD-L1 expression in this rare tumour entity. Patients and methods: We analysed all patients with platinum refractory GCT treated with checkpoint inhibitors at our institutions between 2015 and 2017. Data were retrieved retrospectively from the patient charts. Results: Seven patients were treated with nivolumab or pembrolizumab. Four patients received single-dose treatment and died shortly afterwards due to tumour progression; the remaining three patients received treatment for at least 6 months. No significant treatment toxicity was observed. Long-term tumour response was achieved in two of the three patients, both of them highly positive for PD-L1 staining Interpretation: We consider checkpoint inhibition to be efficient in carefully selected patients with platinum refractory GCT. However, predictive markers associated with tumour response are not yet known and larger prospective clinical trials are warranted.
Gesehen am 06.12.2019